(untitled) (Advancements in Homeopathic Research, 2025)
Diabetic patient taking Homeopathic globules frequently doubt whether it would affect their blood sugar levels. To confirm this homeopathic globule number 40 were subjected to H.P.L.C technique and actual sucrose and lactose consumed per gram of homeopathic globule was evaluated, this sugar level was compared with sucrose and lactose of average size of Himachal Apple of 172.844gm as one apple a day is allowed in most of the diabetic diet plan. It was found experimentally, that apple contains much more sucrose and lactose as compared to single dose of 3 globules of homeopathic medicine and hence it is safe to prescribe homeopathic globules to a Diabetic patient.